The industry response to macroeconomic shocks in the UK, Germany and France and the convergence debate - Cuthbertson, Keith; Hayes, Simon; Hyde, Stuart (Economic & Social Studies, 1998)
In this paper, we investigate the response of stock returns at an industry level to macroeconomic shocks for the UK, Germany and France. The betas between the stock returns and the macroeconomic factors provide a metric for the markets view of the homogeneity of industry response to the various macroeconomic shocks. We find that the market seems to focus on the interest rate and the exchange rate as key sources of important shocks and that shocks to real output growth have little or no direct effect on most industry returns in all three countries.
Keywords: Macroeconomic shocks; Convergence; United Kingdom; France; Germany; Industrial performance